High gain multi-band circularly polarized wearable leaky wave zipper MIMO antenna - Saeidi, Tale; Sahar, Saleh; Mahmood, Sarmad Nozad; Timmons, Nick; Abdullah Al-Gburi, Ahmed Jamal; Karamzadeh, Saeid; Razzaz, Faroq (Elsevier Ltd, 2024)
A miniaturized, multi-band, four-port wearable Multiple Input Multiple Output (MIMO) antenna is proposed, which contains a leaky wave textile antenna (LWTA) on denim (εr = 1.6, tanδ = 0.006) as substrate and Shieldit Super Fabric as conductor textile. The concept in this work involves incorporating the metal and plastic zipper into the garment to function as an antenna worn on the body. Simulations and measurements have been conducted to explore this idea. The LWTA has dimensions of 40 × 30 × 1 mm³. Every two ports are separated by a zipper with two different kinds of materials: Acetal Polymer Plastic (APP) and 90 % brass to improve the isolation, gain, and Impedance bandwidth. The antenna operates in the frequency ranges covering the L, C, S, and X bands. Additionally, diversity performance is evaluated using the Envelope Correlation Coefficient (ECC) and diversity gain (DG). Simulation and measurement findings agree well, with a maximum gain of 12.15 dBi, low Specific Absorption Rate (SAR) based on the standards, DG greater than 9.65 dB, circular polarization (CP), and strong isolation (<-23 dB) between each port. Since the antenna's characteristics do not change significantly under bending and when the zipper is opened, the proposed antenna is a viable candidate for body-centric wireless communications on the battlefield. For example, it can facilitate communication covering wireless local area network (WLAN) and fifth-generation (5G) communications.